(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
This article intends to perform an approach regarding the feasibility or not of Restorative Justice as an adequate instrument to solve conflicts involving Gender Violence. In a first moment it took care of the conceptualization of the term "gender violence", presenting the species and some data that permeate the reality of Brazil. Next, some comments are made about Restorative Justice, in order to define it, observe its implementation and, finally, justify whether it would be a means of combating gender violence. The main objectives of this work are to bring definitions about gender violence and restorative justice; to indicate this as a skillful mechanism for resolving the effects of gender violence in Brazil. The methodology adopted will be the bibliography. Finally, restorative justice is a poor means of addressing these conflicts, since gender violence is a structural and sometimes cultural problem. In this sense, the search for dialogue between the victim and the aggressor would bring unnecessary exposure, and a revictimization of the violated could occur.